Using chain story technique in writing narrative text at the tenth grade students of SMAN 1 Barangka - Shalihi, Wa Ode Cici Malimua; Rohmana, Rohmana; Cahyadin, Wawan (Journal of Teaching of English, 2022)
The objective of this research was to find out whether there was a significant effect of the chain story technique in writing a narrative text at the tenth grade of SMA Negeri 1 Barangka. This research used a pre-experimental design that consisted of one class as a treatment class. The population in this research was the tenth grade of MIA, and the sample of this research was students at the class X Mia 2 of SMAN 1 Barangka in academic years 2020/2021. The sample was taken using purposive sampling, and the total number of students was 20. The research instrument was a writing test that focused on narrative text. The researcher collected the data by giving pre-test, giving treatment in the class using chain story technique, and lastly giving the post-test. The data were analyzed by descriptive statistics and normality tests. For testing the hypothesis, the researcher used paired sample t-test, which was calculated through SPSS 17.0. The result of this research showed that students' mean post-test score was 76.53, which raised 38.33 points from the pre-test (38.20). Additionally, the Sig (2 tailed) was 0.000. It meant that the probability (Sig) value was lower than Î± (p-value < Î± or 0.000<0.05). Therefore, the chain story technique significantly affected students' writing achievement at the tenth-grade students of SMAN 1 Barangka.